Contribution of Learning Attitudes and Learning Motivation to Writing Skills of Exposition Discussion XI Class 1 Batipuh State Vocational School Student - Delfa leli leli; Atmazaki Atmazaki; Abdurahman Abdurahman (International Journal of Educational Dynamics, 2019)
CONTRIBUTION OF LEARNING ATTITUDES AND LEARNING MOTIVATION TO WRITING SKILLS OF EXPOSITION DISCUSSION XI CLASS 1 BATIPUH STATE VOCATIONAL SCHOOL STUDENT Delfa leli 1, Atmazaki 2 Abdurahman 3 Indonesian Language And Literature Education Study Program Graduate program Padang State University E-mail: delfaleli03@gmail.com ABSTRACT This study aims to determine the contribution of learning attitudes and learning motivation towards Writing Skills in Exposition Essay of Class XI Students of State Vocational High School 1 in Full 2015/2016 Academic Year. This research is a type of correlational research. The population in this study were all students of class XI of SMK Country 1 Batipuh which amounted to 187 students by taking samples from members of the population obtained a sample of 65 students. The instruments of this study were questionnaires and performance tests. The results of the validity test of the student learning attitude questionnaire obtained 30 items that were declared valid from 28 items tested. The results of the reliability test obtained a value of r_11 of 0.926, it was concluded that the research instruments used were reliable / reliable. While the learning motivation of the results of the validity test of student learning motivation questionnaire obtained 35 items that were declared valid. The results of the reliability test obtained a value of r_11 of 0.973, it was concluded that the research instruments used were reliable / reliable. The technique of analyzing research data using the Kolmogorov-Smirnov test, multiple correlation test, t test, F test, and determinant coefficient formula. The results of this study are as follows. (1) The attitude of learning contributes to the skill of writing exposition discourse by 10.0%. (2) Motivation to learn contributes to the skill of writing exposition discourse of 14.2%. (3) Learning attitudes and learning motivation together contribute to the skill of writing exposition discourse of 20.5%, in the description of reading habits including more than adequate categories and student learning motivation including more than adequate categories. Conclusions of this study (1) Learning attitudes contribute and a significant positive relationship to exposition discourse writing skills, (2) learning motivation contributes and a significant positive relationship to exposition discourse writing skills, and (3) reading habits and learning motivation together -sama contributes and has a significant relationship to the skills of writing exposition discourse. Keywords: Learning Attitudes, Learning Motivation, and Writing Skills